2000
DOI: 10.12968/jowc.2000.9.8.26017
|View full text |Cite
|
Sign up to set email alerts
|

Influences on patient adherence with compression hosiery

Abstract: Compression hosiery plays a vital role in preventing leg ulcer recurrence, but many patients choose not to wear it. This review identifies the factors that may be responsible for this and suggests how the problem can be overcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In line with previous research (19,22,24–28), significant levels of patient non compliance are reported…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In line with previous research (19,22,24–28), significant levels of patient non compliance are reported…”
Section: Discussionsupporting
confidence: 90%
“… The ulcer and the underlying chronic venous insufficiency are acknowledged as difficult to treat and determining the best approach is not straightforward Many clinicians feel dissatisfied with the care that they can provide for patients with VLU Current compression therapy is not uniformly effective There is inconsistency in the outcomes delivered by compression therapies There was little sign of common treatment approaches or the emergence of any single ‘standard’ In line with previous research (19,22,24–28), significant levels of patient non compliance are reported Treating VLU can be a very rewarding experience for the clinician, but this is often the exception. The greatest degree of feedback from clinicians was of an experience that is dissatisfying and frustrating Clinician dissatisfaction relates to the difficulty in overcoming the key challenges they report; patient compliance and motivating/educating them, dealing with oedema and the chronicity of the underlying condition …”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Lifelong compression therapy is the primary conservative strategy to prevent recurrence, yet in practice, the use of long‐term compression is associated with multiple difficulties and poor rates of adherence (Flaherty 2005). Patients report that compression garments are uncomfortable, costly and difficult to apply (Moffatt & Dorman 1995, Harker 2000, Anand et al. 2003, Seppanen & Livanainen 2005).…”
Section: Introductionmentioning
confidence: 99%